Different decision-making in spine metastasis management among radiation oncologists and orthopedic surgeons: a Korean online survey study - Byun, Hwa Kyung; Koom, Woong Sub; Park, Se-Jun; Kim, Sang-Il; Kim, Jin Ho; Kim, Young-Hoon; Chang, Bong-Soon; Ahn, Yong Chan (Frontiers in Neurology, 2024)
Purpose To understand the current practice of radiation oncologists (ROs) and orthopedic surgeons (OSs) regarding spine metastasis. Methods In 2022, an internet-based survey was conducted for ROs and OSs who treat spinal metastasis in Korea. Respondents were asked to choose the treatment option for two clinical scenarios. Scenario 1 involved a case displaying symptoms of leg weakness due to spinal cord compression and Scenario 2 involved a case with back pain due to pathologic compression fracture. The survey also included a question that required respondents to rank the importance of 11 clinical factors that affect treatment decisions. Results Forty-nine ROs and 30 OSs responded to the survey. There were significant differences in treatment choices between two groups for both scenarios (P = 0.001). In Scenario 1, more OSs chose surgical resection than ROs (43.3% vs. 16.7%), while more ROs chose radiotherapy than OSs (83.3% vs. 53.3%). In Scenario 2, a similar proportion of OSs and ROs chose radiotherapy (OSs, 71.4% vs. ROs, 67.3%), while more OSs opted for prophylactic fixation after radiotherapy than ROs (95.0% vs. 42.4%). The top three factors influencing treatment decisions were general performance status, life expectancy, and spinal instability for both ROs and OSs. In both Scenarios 1 and 2, the treatment decisions of ROs changed significantly when clinical conditions related to these top three factors were altered. Conclusion Although ROs and OSs share the same factors influencing treatment decisions for spinal metastases, notable differences exist in their actual treatment preferences, with ROs preferring radiotherapy and OSs opting for surgical resection. Multidisciplinary discussions may be necessary to reduce the gap in decision-making.